2020
DOI: 10.1007/s10639-020-10110-w
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of learning management systems adoption in Nigeria: A hybrid SEM and artificial neural network approach

Abstract: Research has shown that technology, when used prudently, has the potential to improve instruction and learning both in and out of the classroom. Only a handful of African tertiary institutions have fully deployed learning management systems (LMS) and the literature is devoid of research examining the factors that foster the adoption of LMS. To fill this void, the present research investigates the factors contributing to students' acceptance of LMS. Survey data were obtained from registered students in four Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 55 publications
4
35
0
Order By: Relevance
“…Overall, the identification of content and context dimensions offers a suitable method to shed light on the current adoption state of KMS in educational institutions and the barriers that prevent such adoption [43,106].…”
Section: Intention To Adopt Kms Factors Behavioral Intentionmentioning
confidence: 99%
“…Overall, the identification of content and context dimensions offers a suitable method to shed light on the current adoption state of KMS in educational institutions and the barriers that prevent such adoption [43,106].…”
Section: Intention To Adopt Kms Factors Behavioral Intentionmentioning
confidence: 99%
“…As we have noted before, behavioral intention is influenced by other factors: performance expectancy, effort expectancy, social influence, facility conditions, and habit. Previous studies have shown that behavioral intention has a positive impact on the actual use of technology [1,7,12,49]. In the context of this study, behavioral intention captures students' intention to use the university xRM e-services, so that they can accomplish their activities.…”
Section: Hypothesis 7 (H7) Ht Has a Positive Impact On Students' Actual Use Of Xrm E-servicesmentioning
confidence: 99%
“…Many people are aware that information and communications technology (ICT) plays an important role in the higher education context [1][2][3][4][5][6][7][8][9][10][11][12][13]. Those who were not, had a chance to convince themselves in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as social influence and system/ information quality were investigated as well (Ghazal et al, 2017;Prasad et al, 2018). In research on e-learning alone, factors such as user perceptions and emotions, technical support, system quality and social influence were found to be linked to its effectiveness and adoption (Al-Maroof et al, 2020;Ding and Zhao, 2020;Guo et al, 2016;Lew et al, 2019;Yakubu et al, 2020;Wong et al, 2019). However, studies specifically focussing on the challenges of using OCBL are still limited (Rasheed et al, 2020), especially in the context of Malaysia.…”
Section: Blended Learning and Its Online Componentmentioning
confidence: 99%
“…Perceived usefulness is the degree to which an individual perceives his/her job performance or learning outcome to be facilitated when using the information system (Davis, 1989). This is well-founded when used for assessing users' acceptance of diversified information systems; it also seems to show a positive influence on individuals' intention to use the system (Ghazal et al, 2018;Yakubu et al, 2020). Indeed, with the adoption of the OCBL, students could enjoy massive benefits.…”
Section: Acceptance Behaviourmentioning
confidence: 99%